New method for the synthesis of formaldehyde-free phenolic resins from lignin-based aldehyde precursors. (January 2016) - Foyer, G.; Chanfi, B.-H.; Boutevin, B.; Caillol, S.; David, G.
Graphical abstract: Highlights: The synthesis of resol-type phenolic resins without formaldehyde is presented. The functionalization of bio-based phenolic compounds into aldehyde was investigated. Model reaction in the presence of phenol was carried out. The thermo-stability of the obtained bio-based phenolic resins was established. Abstract: Phenolic resins are mainly obtained from phenol and the highly toxic and volatile formaldehyde. In order to synthesize new formaldehyde substituents for the synthesis of resol-type phenolic resins, we designed a method to functionalize phenolic compounds with aliphatic aldehydes by a two-steps reaction: the functionalization of an acetal group on aromatic hydroxyl functions and the subsequent deprotection of theses acetal groups into aliphatic aldehyde groups. This method was used on the lignin-based aromatic aldehyde precursors i.e. 4-hydroxybenzaldehyde and vanillin to turn them into reactive and difunctional biobased aromatic aldehyde precursors. Those precursors proved to lead to formaldehyde-free and biobased phenolic resins with competitive thermal properties compared to the usual formaldehyde resins.